Modelos viscoelásticos para o estudo de materiais macios com microscopia de força atômica - Sousa, Fabrício Barroso de (2021)
A diversity of materials, let them be synthetic or biological, exhibit viscoelastic behavior, such as cells, and polymers, for example. In this way, it has stood out the nanoindentation experiments by Atomic Force Microscopy (AFM), whose resulting force curves can be described through a convenient theoretical model which makes it possible to obtain the rheological properties of such materials. In celular rheology, for example, there are in the literature various works that employ the AFM to determining the cell hardness through the instantaneous Young’s modulus calculation (Sousa et al., 2017). However, by considering cells as homogenous and isotropic solids, they neglect their structural complexity and viscoelastic nature. Therefore, the present dissertation aims to develop and compare three theoretical models capable of describing the viscoelastic behavior of soft materials when they are indented by an AFM tip with general geometry during three different steps, namely: load, dwell and oscillation. In the former, the tip comes into contact with the sample and presses it until a maximum indentation be reached. After that, in the dwell phase, the indentation is kept constant during a predetermined time. Then, the tip is forced to oscillate over the sample in order to trigger a sinusoidal indentation. This last step characterizes what is know in the literature as dynamic rheology. The objective of this approach is to contribute with the researches about rheology of soft materials based on atomic force microscopy by proposing mathematical models analytically deduced and which have their specificities and flaws well established in order to provide their application in a safe and reliable way.